The Validity and Reliability Questionnaire of Students' Critical Thinking Skills in General Biology Course - Ardi Ardi; Fauziah Hervi; Mudjiran Mudjiran (Jurnal Penelitian Pendidikan IPA, 2023)
Critical thinking skills are very important for biology learning. However, it has not been thoroughly researched because the current evaluation technique cannot test students' critical thinking skills in studying biology. To make it easier for students to apply the concepts they have learned, an evaluation instrument must be made to assess how well they are progressing in developing their critical thinking skills. A valid and reliable critical thinking questionnaire is the goal of this study. The type of research used is called research and development (R&D). Based on the findings of the validity test, the resulting evaluation tool has 31 valid statements and 5 invalid statements with a reliability value of 0.93 which is included in the very high category. In general biology classes, the instruments developed can evaluate students' critical thinking skills. Therefore, it can be concluded that a questionnaire designed to measure students' critical thinking skills in general biology courses is feasible to use.